Academic freedom in Europe: Limitations and judicial remedies - Kriszta Kovács (Global Constitutionalism, 2024)
Europe has recently struggled with democratic backsliding and autocratization. This autocratization has accompanied a decline in academic freedom in many backsliding countries, as reported by the Academic Freedom Index. Can the standards set by the European supranational courts effectively safeguard academic freedom? This article provides answers to this question. It argues that despite differences in their approaches, the theoretical conceptions of scholarship held by the European Court of Human Rights (ECtHR) and the Court of Justice of the European Union (ECJ) share an essential feature: both have moved towards embracing the `liberal science script' by protecting academic freedom. The main difference between the two courts' approaches is the subject of protection. The ECtHR focuses on the individual rights of academics: It protects free speech in the academic context by establishing a high standard for holding academics liable for publicly expressing their views inside and outside of academia. The ECJ has applied the concept of institutional autonomy, thereby setting a high standard for safeguarding the freedom of academic institutions. This standard can be applied with regard to the demands placed by policy-makers on academia regarding its role in democracy, including gender equality requirements for EU research funding.
Keywords: 320; academic freedom; EU Charter of Fundamental Rights; European Convention on Human Rights; free speech in the academic context; limitations of scientific research